The Distribution and Origins of Canadian Natives in the Old Northwest in 1850 - Rose, Gregory (Ontario History)

(untitled) (The Ontario Historical Society, 2026)
In 1850, the number of Canadians in each Old Northwest state in the United States varied considerably, partly due to differences in total population (Ohio had nearly two million people and Wisconsin about 305,000), and partly due to differences in settlement preferences. Indiana’s total population was nearly triple that of Michigan, but Michigan housed over seven times as many Canadians. The residential locations of the Old Northwest’s British American immigrants can be examined at two levels. First, generally, by considering each state’s number of Canadians and their proportions compared to all immigrants (domestic and foreign), only foreign immigrants, and within the total of British Americans. Second, more granularly, by analyzing their county-by-county residential locations. Since published census tables do not include county-level nativity data, this information was extracted from the microfilmed schedules through individual-by-individual counting and data analysis. The 1850 manuscript census also provides a window into the origins of immigrants to the Old Northwest within British America. Census records reveal that British American immigrants lived in nearly every county of the Old Northwest in 1850, and in many Michigan, Wisconsin, and northern Illinois counties, they represented a significant proportion. Yet they are scarcely examined in the historical literature. Perhaps this article can point researchers towards places where local histories and genealogical information can be examined to construct a deeper understanding of the presence and role of mid-nineteenth century Canadian immigrants to the Old Northwest.